THE PROBLEM OF SUPPLIER - Raffo Lecca, Eduardo (1999)
This is a famous problem from the annals of literature in operations research. G. Dantzig in [1] refers to W.W. Jacobs with his paper "The Caterer Problem" Nav. Log Res. Quart. 1 1954; as well as Gaddum, Hoffman and Sokolowsky "On the Solution of the Caterer Problem" Naval Res Logist. Quart., Vol.1, No. 3, september, 1954, and William Prager "On the Caterer Problem" of Management Sci, Vol 3, No. 1 october 1956 and Management Sci, Vol 3, No. 2 january 1957. Subsequently both G. Hadley presents the subject in his "Linear Prograrriming" [2], as Walter Garvin in his Introduction as Linear Programming "presented the topic.